Electronic Structure Regulation of Layered Vanadium Oxide via Interlayer Doping Strategy toward Superior High‐Rate and Low‐Temperature Zinc‐Ion Batteries - Geng, Hongbo; Cheng, Min; Wang, Bo; Yang, Yang; Zhang, Yufei; Li, Cheng Chao (Advanced functional materials, 2020)
Currently, development of suitable cathode materials for zinc‐ion batteries (ZIBs) is plagued by the sluggish kinetics of Zn2+ with multivalent charge in the host structure. Herein, it is demonstrated that interlayer Mn2+‐doped layered vanadium oxide (Mn0.15V2O5·nH2O) composites with narrowed direct bandgap manifest greatly boosted electrochemical performance as zinc‐ion battery cathodes. Specifically, the Mn0.15V2O5·nH2O electrode shows a high specific capacity of 367 mAh g−1 at a current density of 0.1 A g−1 as well as excellent retentive capacities of 153 and 122 mAh g−1 after 8000 cycles at high current densities up to 10 and 20 A g−1, respectively. Even at a low temperature of −20 °C, a reversible specific capacity of 100 mAh g−1 can be achieved at a current density of 2.0 A g−1 after 3000 cycles. The superior electrochemical performance originates from the synergistic effects between the layered nanostructures and interlayer doping of Mn2+ ions and water molecules, which can enhance the electrons/ions transport kinetics and structural stability during cycling. With the aid of various ex situ characterization technologies and density functional theory calculations, the zinc‐ion storage mechanism can be revealed, which provides fundamental guidelines for developing high‐performance cathodes for ZIBs. Vanadium oxide pillared by interlayer doping of Mn2+ ions and water is synthesized through a facile microwave‐assisted strategy. When evaluated as a cathode for zinc‐ion batteries, the as‐prepared electrode delivers superior zinc‐ion storage properties in terms of high specific capacity, stable cycling capability, excellent rate, and low‐temperature performance.